ANALISA PENGARUH DESTINATION IMAGE, PERCEIVED SATISFACTION, SERVICE QUALITY, PRICE, DAN EXPERIENCE TERHADAP REVISIT INTENTION MASYARAKAT BATAM KE NEGARA TETANGGA SINGAPURA DAN MALAYSIA - Pulung Peranginangin; Hepy Hefri, Ariyanto, Surianti (CV. ADIBA AISHA AMIRA, 2023)
The proximity of Batam City to Singapore and Malaysia makes Singapore and Malaysia very popular tourist destinations for the people of Batam. The increase in the population of Batam creates a greater potential for people to travel abroad. This research intends to determine the factors influencing the intention to revisit neighboring countries such as Singapore and Malaysia. The objects of this research include all residents of Batam who have traveled to Singapore or Malaysia, without being limited by gender, age, occupation, education level, or income level of the respondents. The samples were taken using the purposive sampling method by distributing questionnaires online using Google Forms to 170 respondents. Data in this research was collected for the last year before the research was conducted, from 2022 to 2023. The collected data was then processed using SPSS software. In this research, it was found that destination image, service quality, price, and experience significantly influence the revisit intention. At the same time, perceived satisfaction does not have a significant influence and is different from the initial hypothesis of the test